Lomentospora prolificans fungemia in hematopoietic stem cell transplant patients: First report in South America and literature review. Issue 4 (9th May 2018) - Penteado, Fernando D.; Litvinov, Nadia; Sztajnbok, Jaques; Thomaz, Danilo Y.; dos Santos, Antonio M.; Vasconcelos, Dewton M.; Motta, Adriana L.; Rossi, Flávia; Fernandes, Juliana F.; Marques, Heloisa Helena S.; Benard, Gil; de Almeida, João N.
Abstract: Lomentospora prolificans is a filamentous fungus and an emerging pathogen in immunocompromised patients. It is encountered most commonly in Australia, Spain, and USA. We described the first case of Lomentospora prolificans fungemia in South America. The patient was a hematopoietic stem cell transplantation (HSCT) recipient who developed the infection 37 days after stem cells infusion. In addition, we performed a literature review of invasive lomentosporiosis in HSCT patients.